2012
DOI: 10.1155/2013/193671
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Cephalexin in Ionic Liquid Aqueous Two‐Phase System Composed of 1‐Butyl‐3‐Methylimidazolium Tetrafluoroborate and ZnSO4

Abstract: Ionic liquid aqueous two-phase system (ILATPS) was applied in the extraction and separation of hydrosoluble antibiotics. The partitioning behavior of cephalexin (CEX) in 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4)-ZnSO4aqueous two-phase system was studied by the partitioning parameter of the extraction efficiency. The effect of the volume of [Bmim]BF4, the concentration of ZnSO4, temperature, pH, and the volume of ZnSO4solution was discussed concretely. When the volume of [Bmim]BF4was 2 mL and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In these studies, [C 4 C 1 im]­Cl, [C 4 C 1 im]­[BF 4 ], and [C 4 C 1 im]­Br were used, with NaH 2 PO 4 as the salting-out agent and two distinct lines of research were adopted: while Liu and co-workers extracted penicillin G from a filtered fermentation broth with efficiencies higher than 90%, Jiang and collaborators addressed the approaches applied to isolate this antibiotic by adding an hydrophobic IL, as described in Figure B. In addition to tetracycline and penicillin G, other antibiotics were also studied, namely ciprofloxacin and its hydrochloride salt, , cephalexin, and chloramphenicol. , Of particular interest is the work of Han et al, which followed an emergent green tendency of applying a less toxic and more biodegradable organic salt, such as K 2 C 4 H 4 O 6 , as a replacement for the typically used inorganic salts.…”
Section: Pharmaceuticals and Drugsmentioning
confidence: 99%
“…In these studies, [C 4 C 1 im]­Cl, [C 4 C 1 im]­[BF 4 ], and [C 4 C 1 im]­Br were used, with NaH 2 PO 4 as the salting-out agent and two distinct lines of research were adopted: while Liu and co-workers extracted penicillin G from a filtered fermentation broth with efficiencies higher than 90%, Jiang and collaborators addressed the approaches applied to isolate this antibiotic by adding an hydrophobic IL, as described in Figure B. In addition to tetracycline and penicillin G, other antibiotics were also studied, namely ciprofloxacin and its hydrochloride salt, , cephalexin, and chloramphenicol. , Of particular interest is the work of Han et al, which followed an emergent green tendency of applying a less toxic and more biodegradable organic salt, such as K 2 C 4 H 4 O 6 , as a replacement for the typically used inorganic salts.…”
Section: Pharmaceuticals and Drugsmentioning
confidence: 99%
“…For instance, Han and co-workers determined the liquid–liquid equilibrium data for the IL ATPSs containing the [C n mim] BF 4 with different carbon-chain lengths and inorganic salts . The effect of temperature also be considered in 1-butyl-3-methylimidazolium tetrafluoroborate-salts aqueous two-phase systems. , Additionally, the systems [C n mim]Br ( n = 4,6,8,10,12), [C 4 mim]­[PF 6 ] and 1-decyl-3-bromide + salt + water have been reported by Wang et al The structures and properties of ILs can be adjusted finely by changing the cation or anion of the IL, and specific functionality can be introduced to the IL. Several researchers have indicated that pyridinium ionic liquids also exhibit good extraction and separation properties.…”
Section: Introductionmentioning
confidence: 99%